Vascular smooth muscle cells derived from inbred swine induced pluripotent stem cells for vascular tissue engineering. (December 2017) - Luo, Jiesi; Qin, Lingfeng; Kural, Mehmet H.; Schwan, Jonas; Li, Xia; Bartulos, Oscar; Cong, Xiao-qiang; Ren, Yongming; Gui, Liqiong; Li, Guangxin; Ellis, Matthew W.; Li, Peining; et al.
Abstract: Development of autologous tissue-engineered vascular constructs using vascular smooth muscle cells (VSMCs) derived from human induced pluripotent stem cells (iPSCs) holds great potential in treating patients with vascular disease. However, preclinical, large animal iPSC-based cellular and tissue models are required to evaluate safety and efficacy prior to clinical application. Herein, swine iPSC (siPSC) lines were established by introducing doxycycline-inducible reprogramming factors into fetal fibroblasts from a line of inbred Massachusetts General Hospital miniature swine that accept tissue and organ transplants without immunosuppression within the line. Highly enriched, functional VSMCs were derived from siPSCs based on addition of ascorbic acid and inactivation of reprogramming factor via doxycycline withdrawal. Moreover, siPSC-VSMCs seeded onto biodegradable polyglycolic acid (PGA) scaffolds readily formed vascular tissues, which were implanted subcutaneously into immunodeficient mice and showed further maturation revealed by expression of the mature VSMC marker, smooth muscle myosin heavy chain. Finally, using a robust cellular self-assembly approach, we developed 3D scaffold-free tissue rings from siPSC-VSMCs that showed comparable mechanical properties and contractile function to those developed from swine primary VSMCs. These engineered vascular constructs, prepared from doxycycline-inducible inbred siPSCs, offer new opportunities for preclinical investigation of autologous human iPSC-based vascular tissues for patient treatment.